2003
DOI: 10.1002/pmic.200300577
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of differentially expressed proteins induced by rice blast fungus and elicitor in suspension‐cultured rice cells

Abstract: We used two-dimensional electrophoresis (2-DE) and other proteomic approaches to identify proteins expressed in suspension-cultured rice cells in response to the rice blast fungus, Magnaporthe grisea. Proteins were extracted from suspension-cultured cells at 24 and 48 h after rice blast fungus inoculation or treatment with elicitor or other signal molecules such as jasmonic acid (JA), salicylic acid, and H(2)O(2). The proteins were then polyethylene glycol fractionated before separation by 2-DE. Fourteen prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
133
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(139 citation statements)
references
References 53 publications
3
133
2
1
Order By: Relevance
“…The fact that this difference was only apparent 1 hr after release suggests that JA-induced rice volatiles were slightly attractive to female N. lugens, whereas JA-induced nonvolatile chemicals had no particular effect on host preference. The latter is somewhat surprising as JA elicitation increases the production of proteinase inhibitors, phytoalexins, and PRs in rice plants (Rakwal and Komatsu, 2000;Rakwal et al, 2001;Kim et al, 2003). N. lugens female adults are attracted to limonene (Lou et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that this difference was only apparent 1 hr after release suggests that JA-induced rice volatiles were slightly attractive to female N. lugens, whereas JA-induced nonvolatile chemicals had no particular effect on host preference. The latter is somewhat surprising as JA elicitation increases the production of proteinase inhibitors, phytoalexins, and PRs in rice plants (Rakwal and Komatsu, 2000;Rakwal et al, 2001;Kim et al, 2003). N. lugens female adults are attracted to limonene (Lou et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…In rice, the world's most important food crop, the role of JA signaling has been mainly studied for direct defenses. Exogenous application of JA on rice plants elicits the productions of proteinase inhibitors, phytoalexins, PRs, and salt-induced proteins (Tamogamia et al, 1997;Rakwal and Komatsu, 2000;Rakwal et al, 2001;Kim et al, 2003), and it may increase the emission of volatiles (Obara et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, five proteins (D1, D6-D8 and D10) appeared only on the control gel. In a previous report, proteomic analysis of rice suspension culture cells treated with rice blast fungus 25 also detected a 31.1 kDa (pI 4.98) protein, which was identified as putative receptor-like kinase. The same author also found an increase in the amount of 33.8 kDa proteins with pI of 4.73 and 4.79, which was identified as salt induced protein, SalT.…”
Section: Resultsmentioning
confidence: 99%
“…In general, both beta-glucanases and peroxidases have been known as enzymes that mediate the defense system against abiotic stresses such as ozone, H 2 O 2 and ultraviolet radiation (Cheong et al, 2000;Dabir et al, 2007;Kim et al, 2008b;Thalmair et al, 1996). The tags for PR-10 ( Kim et al, 2003;McGee et al, 2001;Tanaka et al, 2003) were detected a total of three times, suggesting that the protein seems to make a significant contribution as a biotic stress defense system. Recently, it was reported that the JIOsPR10 protein which is one of the PR-10 family possesses RNase activity that is dependent on sensitive to DTT, suggesting the importance of the disulfide bonding between cysteine residues (Kim et al, 2008a).…”
Section: Resultsmentioning
confidence: 99%